Cervical spondylotic myelopathy: diagnostic performance of radiologists with varying levels of experience in comparing MR images acquired using field strengths of 1.5 and 3 Tesla. (October 2019) - Shim, Euddeum; Lee, Joon Woo; Lee, Eugene; Kang, Yusuhn; Kang, Heung Sik; Kang, Woo Young; Im, Tae Seong
Background: Although both 1.5-Tesla (T) and 3-T magnetic resonance imaging (MRI) are widely used for the diagnosis of cervical spondylotic myelopathy (CSM), there have been no comparative studies. Purpose: This study compared the performance of both imaging modalities for diagnosing CSM among radiologists with varying experience levels. Material and Methods: Four independent readers with different levels of experience reviewed 1.5-T and 3-T MR images of 79 patients with cervical spondylopathies. For both field strengths, images were evaluated for the depiction of intramedullary T2 hyperintensity of the cord according to disc level using a 5-point scale: –2 = definitely absent; –1 = probably absent; 0 = equivocally absent or present; 1 = probably present; and 2 = definitely present. The score was transformed into a 3-point certainty scale, which converted to absolute value (0 = equivocal, 1 = probable, 2 = definite lesion). Linear mixed model statistics were used to compare the depiction and certainty scale between 1.5-T and 3-T images. Inter-observer agreement was assessed by using Kendall's W statistics. Results: Inter-observer agreements among the four readers were 0.718 for 1.5-T and 0.784 for 3-T MR images. Diagnostic accuracy of each reader was slightly increased using 3-T and varied regardless of level of reader experience. The certainty of CSM diagnosis was significantly improved using 3-T field strength. Equivocal lesions were significantly decreased in 3-T MRI in all readers. Conclusion: Compared with 1.5-T MRI, 3-T imaging increased the certainty of the lesion and decreased the number of equivocal lesions in patients with CSM. Diagnostic accuracy was not affected by levels of reader experience.